Spatial patterns in the oxygen isotope composition of daily rainfall in the British Isles - Tyler, Jonathan J.; Jones, Matthew D.; Arrowsmith, Carol; Allott, Tim; Leng, Melanie J. (Springer, 2015)
Understanding the modern day relationship between climate and the oxygen isotopic composition of precipitation (δ18OP) is crucial for obtaining rigorous palaeoclimate reconstructions from a variety of archives. To date, the majority of empirical studies into the meteorological controls over δ18OP rely upon daily, event scale, or monthly time series from individual locations, resulting in uncertainties concerning the representativeness of statistical models and the mechanisms behind those relationships. Here, we take an alternative approach by analysing daily patterns in δ18OP from multiple stations across the British Isles (n = 10–70 stations). We use these data to examine the spatial and seasonal heterogeneity of regression statistics between δ18OP and common predictors (temperature, precipitation amount and the North Atlantic Oscillation index; NAO). Temperature and NAO are poor predictors of daily δ18OP in the British Isles, exhibiting weak and/or inconsistent effects both spatially and between seasons. By contrast δ18OP and rainfall amount consistently correlate at most locations, and for all months analysed, with spatial and temporal variability in the regression coefficients. The maps also allow comparison with daily synoptic weather types, and suggest characteristic δ18OP patterns, particularly associated with Cylonic Lamb Weather Types. Mapping daily δ18OP across the British Isles therefore provides a more coherent picture of the patterns in δ18OP, which will ultimately lead to a better understanding of the climatic controls. These observations are another step forward towards developing a more detailed, mechanistic framework for interpreting stable isotopes in rainfall as a palaeoclimate and hydrological tracer.